The influence of habitat edge on a ground nesting bird species: hen harrier Circus cyaneus. Issue 2 (16th June 2020) - Sheridan, Kathryn; Monaghan, Jason; Tierney, T. David; Doyle, Susan; Tweney, Charles; Redpath, Steve M.; McMahon, Barry J.
Abstract : Anthropogenic‐source habitat fragmentation leads to increased habitat edge in the environment, with potential negative consequences for wildlife. We examine the influence of increased edge on a ground nesting bird of conservation concern, the hen harrier Circus cyaneus . Using eight years of data collected in the Slieve Bloom Mountains Special Protection Area, central Ireland, and an average breeding population of ten pairs, we investigate how habitat fragmentation and edge influences hen harrier nest site selection, breeding success and productivity. We also used a deterministic population matrix model to assess population breeding trends and to simulate population growth rate responses to increased habitat edge by varying demographic parameters such as productivity and juvenile survival. Our results show that habitat edge had a significant effect on nest site selection, breeding success and productivity. Hen harriers were more likely to nest in areas of high edge/area ratio, but this was associated with lower breeding success and productivity, suggesting a possible ecological trap. This mismatch between nest site selection and breeding output may be linked to this species' high reproductive site fidelity. Our population matrix indicated a population increase, whereas population monitoring indicates population stability. Our simulations suggest that increased edge will have a negative effect on population growth rate, providing a greater understanding of the relationship between hen harrier population trends and changing habitat configuration. These results highlight the importance of contiguous habitats and the need for appropriate land use management in protected upland areas for breeding raptors. Minimising habitat fragmentation and forest edge to create larger blocks of uniform peatland habitat should be an integral part of the conservation management of hen harrier breeding areas both in Ireland and in similar breeding habitats such as those in Britain.